Extracellular tannase from Emericella nidulans showing hypertolerance to temperature and organic solvents - Goncalves, Heloisa Bressan [UNESP]; Riul, Alana Jacomini [UNESP]; Terenzi, Hector Francisco; Jorge, Joao Atilio; Souza Guimaraes, Luis Henrique (Elsevier B.V., 2011)
The filamentous fungus Emericella nidulans (=Aspergillus nidulans) produced high levels of extracellular tannase when grown at 30 degrees C, under agitation (100 rpm), for 24 h in Khanna medium supplemented with tannic acid as carbon source. The enzyme was purified 61-fold, with 30% yield. The molecular mass of the native protein was estimated to be 302 kDa by gel filtration, with a carbohydrate content of 50%. Two protein bands (45.8 and 52 kDa) were observed after 12% SDS-PAGE, suggesting a glycoprotein constituted by three copies of each subunit. The extracellular tannase showed temperature and pH optima of 45 degrees C and 5.0, respectively, and was fully stable in the temperature range of 22-50 degrees C. with a half-life (t(50)) of about 72h at 90 degrees C. The enzyme retained around 80% of control activity when maintained for 60h at pH 4.0 or 5.0. Tannase activity was stimulated by Zn(2+), Hg(2+), Co(2+), and the detergents SDS and Triton X-100. Organic solvents (about 50%, v/v) also increased enzyme activity, particularly isopropanol, acetonitrile, and ethanol. The K(m) and V(max) values were 14.01 mM and 2.63 U mg(-1) protein in the presence of tannic acid; and 4.78 mM and 0.29 U mg(-1) protein in the presence of methyl gallate. For propyl gallate, the V(max) was 0.05 U mg(-1) protein, with K(m) of 7.69 mM; for pyrogallol, the V(max) was 7.40 U mg(-1) protein and the K(m) was 16.94 mM. Crown Copyright (C) 2011 Published by Elsevier B.V. All rights reserved.
Keywords: Tannase; Tannin acyl hydrolase; Emericella; Hyperstable enzyme; Fungi